The Anatomy of Industrial Decline: Productivity, Investment, and Location in U.S. ManufacturingThe Anatomy of Industrial Decline: Productivity, Investment, and Location in U.S. Manufacturing, by Ullmann John E.. Westport, CT: Quorum Books, 1988, 216 pp., $39.95, cloth. - Khandekar, Rajendra P. (Academy of Management Review, 1991)
The article reviews the book ?The Anatomy of Industrial Decline: Productivity, Investment, and Location in U.S. Manufacturing,? by John E. Ullmann.